Entrepreneurial artisan products as regional tourism competitiveness - Teixeira, Sérgio J. (2022)
Purpose – The purpose of this paper is to explore and analyse the role of entrepreneurial artisan products in regional tourism competitiveness. Design/methodology/approach – This study applies secondary data from different sources (Regional Directorate of Statistics of Madeira, the Madeira Institute of Wine, Embroideries and Handicrafts) covering a temporal period spanning the last 15 years (2001-2015). This deployed quantitative data analysis through an econometric approach with recourse to regression models and the Pearson’s correlation technique. Findings – According to the results, it is suggested that in terms of external support and funding, there should be a greater role and a boost in the number of projects carried out not only under the auspices of the European Union but also under the Autonomous Region of Madeira. Thus, participant companies may invest in greater business efficiency and entrepreneurship, in innovation, promotion and the internationalisation of their products, and thereby obtain greater overall regional competitiveness. Research limitations/implications – The generalisation of results remains to a certain extent limited, given the findings stem from only one particular region. The exclusive utilisation of secondary data may also undermine the robustness of the results obtained. Originality/value – The study provides empirical evidence that helps in identifying the role of artisan products within the capacity for regional tourism sector entrepreneurship and competitiveness. Furthermore, this also contributes to the knowledge of the scientific community particularly interested in artisan and cultural entrepreneurship and regional competitiveness in the tourism sector.